Gestational weight gain in the REVAMP pregnancy cohort in Western India: Comparison with international and national references - Dangat, Kamini; Gupte, Sanjay; Wagh, Girija; Lalwani, Sanjay; Randhir, Karuna; Madiwale, Shweta; Pisal, Hemlata; Kadam, Vrushali; Gundu, Shridevi; Chandhiok, Nomita; Kulkarni, Bharati; Joshi, Sadhana; et al. (Frontiers in Medicine, 2022)
Objective To determine the trimester specific gestational weight gain (GWG) in a population of pregnant women from Western India and compare it with the Intergrowth–21st international and an Indian reference (GARBH–Ini cohort—Group for Advanced Research on BirtH outcomes). Study design A prospective longitudinal observational study was undertaken in Pune, West India and data for gestational weight gain was collected [the REVAMP study (Research Exploring Various Aspects and Mechanisms in Preeclampsia)]. Generalized Additive Models for Location, Scale and Shape method (GAMLSS model) were used to create GWG centile curves according to gestational age, stratified by BMI at recruitment (n = 640) and compared with Intergrowth-21st reference and GARBH–Ini cohort. Multivariable regression analysis was used to evaluate the relationship between GWG and antenatal risk factors. Results The median GWG was 1.68, 5.80, 7.06, and 11.56 kg at gestational ages 18, 26, 30, and 40 weeks, respectively. In our study, pregnant women gained less weight throughout pregnancy compared to Intergrowth-21st study, but more weight compared to the GARBH–Ini cohort centile curves in all the BMI categories. GWG in overweight/obese women (BMI ≥ 25) was significantly lower (<0.001) as compared to underweight (BMI < 18.5), or normal weight women (BMI ≥ 18.5 and <25). The median GWG at 40 weeks in underweight, normal and overweight/obese women was 13.18, 11.74, and 10.48 kg, respectively. Higher maternal BMI, older maternal age, higher parity and higher hemoglobin concentrations were associated with lower GWG, while taller maternal height was associated with greater GWG. Conclusion GWG of Indian women is lower than the prescriptive standards of the Intergrowth charts.